Human dendritic cell activation induced by a permannosylated dendron containing an antigenic GM3-lactone mimetic - Ribeiro-Viana, Renato; Bonechi, Elena; Rojo, Javier; Ballerini, Clara; Comito, Giuseppina; Richichi, Barbara; Nativi, Cristina (Beilstein Journal of Organic Chemistry, 2014)
Vaccination strategies based on dendritic cells (DCs) armed with specific tumor antigens have been widely exploited due the properties of these immune cells in coordinating an innate and adaptive response. Here, we describe the convergent synthesis of the bifunctional multivalent glycodendron 5, which contains nine residues of mannose for DC targeting and one residue of an immunogenic mimetic of a carbohydrate melanoma associated antigen. The immunological assays demonstrated that the glycodendron 5 is able to induce human immature DC activation in terms of a phenotype expression of co-stimulatory molecules expression and MHCII. Furthermore, DCs activated by the glycodendron 5 stimulate T lymphocytes to proliferate in a mixed lymphocytes reaction (MLR).
Keywords: cancer immunotherapy; DC-SIGN; DC targeting; glycodendron; GM3-lactone mimetic; multivalent glycosystems; multivalent interactions